2014
DOI: 10.1248/bpb.b13-00703
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Nanoparticles with Physical Stimuli toward Cancer Therapy

Abstract: Drug delivery systems represent an important strategy for cancer treatment. The targeted delivery of drugs is required for effective and safe cancer therapy. In cancer therapy, the target cells include cancer cells and immunocompetent cells such as antigen presenting cells. Anticancer drugs utilized include small molecular drugs, proteins and nucleic acid medicines. In order to deliver these drugs into the target cells, various nanoparticles have been developed. However, the efficacy of the nanoparticulate sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…We have previously demonstrated that pressure as a physical stimulus induces transient cellular membrane permeation and activation of nuclear factor (NF)-jB and activator protein 1 (AP-1) in vivo using the tissue pressure method (Mukai et al, 2010). Because temporary deformations of tissue by pressure and suction are considered to be similar (Shimizu et al, 2012;Fumoto & Kawakami, 2014), we hypothesized that the same phenomena would occur. However, there are few reports about the renal suction method.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that pressure as a physical stimulus induces transient cellular membrane permeation and activation of nuclear factor (NF)-jB and activator protein 1 (AP-1) in vivo using the tissue pressure method (Mukai et al, 2010). Because temporary deformations of tissue by pressure and suction are considered to be similar (Shimizu et al, 2012;Fumoto & Kawakami, 2014), we hypothesized that the same phenomena would occur. However, there are few reports about the renal suction method.…”
Section: Introductionmentioning
confidence: 99%
“…110,111) The pH-sensitive peptide GALA occurs as a random coil conformation at pH 7, whereas it converted to an amphipathic α-helix structure at pH 5. 112) This conformational change of GALA assisted the endosomal escape of PEGylated liposomes to the cytosol.…”
Section: Perspectivesmentioning
confidence: 99%
“…Recently, targeted delivery using an external stimuli-responsive drug delivery system (DDS) has attracted attention. Ultrasound is a type of external energy that is widely used for medical diagnostics, can be applied for clinical uses, and safely reaches the deeper tissues of the human body [1]. In the field of ultrasound-responsive DDS, the targeted delivery into the brain using bubble formulations and ultrasound irradiation has been reported to be successful because of disruption of the blood-brain barrier (BBB) [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%